2018
DOI: 10.1212/wnl.0000000000005167
|View full text |Cite
|
Sign up to set email alerts
|

Peak perihemorrhagic edema correlates with functional outcome in intracerebral hemorrhage

Abstract: Our findings suggest that peak PHE volume represents an independent predictor of functional outcome after ICH. Inflammatory processes and hematoma expansion seem to be involved in PHE evolution and may represent important treatment targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
71
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 41 publications
6
71
1
2
Order By: Relevance
“…It was with great interest that we read the publication by Iglesias-Rey et al [1], who found an association of elevated body temperature with perihemorrhagic edema (PHE) evolution exclusively in hypertension-related intracerebral hemorrhage (ICH). In accordance with pathophysiologic findings, others found an independent association of PHE evolution with inflammatory parameters including fever in ICH without further etiological differentiation [2,3].…”
supporting
confidence: 72%
See 1 more Smart Citation
“…It was with great interest that we read the publication by Iglesias-Rey et al [1], who found an association of elevated body temperature with perihemorrhagic edema (PHE) evolution exclusively in hypertension-related intracerebral hemorrhage (ICH). In accordance with pathophysiologic findings, others found an independent association of PHE evolution with inflammatory parameters including fever in ICH without further etiological differentiation [2,3].…”
supporting
confidence: 72%
“…Furthermore, a larger sample size may be necessary to detect mechanisms related to PHE evolution in subgroups of ICH patients (e.g. CAA-related) due to the complex pathophysiological processes associated with PHE [2,3,6].…”
mentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) may also predict hematoma volume and extension by detecting markers of cerebral small vessel disease (Boulouis et al, ). Finally, perihemorrhagic edema has been found to be an independent predictor of functional outcome after ICH (Volbers et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…NPub.org/cmelist Relative perihemorrhagic edema (PHE) size (edema to hematoma ratio [rPHE]) on admission CT (aCT) as well as peak PHE during the hospital course have been associated with functional outcomes at 90 days in patients with intracerebral hemorrhage (ICH). 1,2 These findings make PHE a candidate target for interventions aiming to improve outcome after ICH. 1,3 One potential modifier of PHE are statins, which were shown to decrease the extent of PHE on aCT in patients who used them before ICH onset, but this finding was not reproducible across studies.…”
Section: Cme Coursementioning
confidence: 99%